Assembly and secretion of heavy chains that do not associate posttranslationally with immunoglobulin heavy chain-binding protein (The Rockefeller University Press, 1987)
Heavy chain-binding protein (BiP) associates posttranslationally with nascent Ig heavy chains in the endoplasmic reticulum (ER) and remains associated with these heavy chains until they assemble with light chains. The heavy chain-BiP complex can be precipitated by antibody reagents against either component. To identify sites on heavy chain molecules that are important for association with BiP, we have examined 30 mouse myelomas and hybridomas that synthesize Ig heavy chains with well characterized deletions. Mutant Ig heavy chains that lack the CH1 domain could not be demonstrated to associate with BiP, whereas mutant Ig heavy chains with deletions of the CH2 or CH3 domain were still able to associate with BiP. In two light chain negative cell lines that produced heavy chains with deletions of the CH1 domain, free heavy chains were secreted. When Ig assembly and secretion were examined in mutants that did not associate with BiP, and were compared with normal parental lines, it was found that the rate of Ig secretion was increased in the mutant lines and that the Ig molecules were secreted in various stages of assembly. In one mutant line (CH1-) approximately one-third of the secreted Ig molecules were incompletely assembled, whereas the Ig molecules secreted by the parental line were completely assembled. Our data show the CH1 domain to be important for association with BiP and that when this association does not occur, incompletely assembled heavy chains can be secreted. This implies a role for BiP in preventing the transport of unassembled Ig molecules from the ER.